2022
DOI: 10.3389/fpsyg.2022.881799
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Health Education, Delivered as Animation Videos, on Postoperative Anxiety and Pain in Femoral Fractures

Abstract: ObjectiveThis article explores the effect of preoperative health education, in the form of animation videos, on postoperative self-reported pain levels and anxiety in femoral fractures.MethodsNinety cases of femoral fracture were divided at random into the oral instruction group, the recorded video group, and the animation video group, with 30 cases in each group. Sociodemographic data were collected the day before surgery. Health education was then offered in one of three ways: orally, using a recorded video,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“… 27 Therefore, providing effective PE methods to assist them can save time 17 and workload. 12 Analyzing patient satisfaction in Table 7 reveals high satisfaction with SPE-VATS, particularly in terms of Intention to Use, Recommendation, Perceived Usefulness, Perceived Ease of Use, and Image scale scores, averaging 4.4 points. This confirms that SPE-VATS is effective in facilitating PE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 Therefore, providing effective PE methods to assist them can save time 17 and workload. 12 Analyzing patient satisfaction in Table 7 reveals high satisfaction with SPE-VATS, particularly in terms of Intention to Use, Recommendation, Perceived Usefulness, Perceived Ease of Use, and Image scale scores, averaging 4.4 points. This confirms that SPE-VATS is effective in facilitating PE.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education (PE) has been proven to successfully reduce anxiety in patients and their families, better prepare them for postoperative issues, improve their compliance with medical advice, reduce pain, increase self-efficacy, and support their activities during the postoperative recovery phase. 5 , 8 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] In addition, studies have found that can lead to better treatment for children. [17] We recommend the use of animated video education combined with bundled care intervention in children with severe pneumonia, which is an innovative way of care.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that in this study, the lowest score on the medical management of illness dimension of self-management was 1, indicating that some patients had a significant lack of knowledge related to anxiety symptom recognition, medication management and emotional management. This reminds healthcare professionals that they should increase education on disease related knowledge for anxious patients, such as through some online live video courses, graphic knowledge push or offline health talks and discharge education, so as to improve patients' disease knowledge and promote self-management [28][29][30].…”
Section: Current Status Of Self-management In Patients With Anxiety D...mentioning
confidence: 99%